Interview - Human Trafficking in Brazil: Between crime-based and human rights-based governance - Ela Wiecko V. de Castilho (Anti-Trafficking Review, 2015)
This interview with Ela Wiecko V. de Castilho, Vice-Prosecutor General of the Republic in Brazil, looks at the development of anti-trafficking law and agendas since Brazil’s ratification of the United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons Especially Women and Children (Trafficking Protocol). Castilho looks at how the externally-imposed concept of anti-trafficking gained momentum in the country and details debates and tensions in the subsequent development of national policy. Brazilian criminal law has significant conceptual differences with the Trafficking Protocol, particularly around consent and internal trafficking. Castilho discusses unresolved issues on rights of sex workers and migrants and points to a data collection methodology that was recently established and will allow for analysis of whether victims’ situations meet the international definition of human trafficking. If they do not, she suggests that this definition may not need to be maintained in Brazil.